Finite element analysis of a free-standing staircase (2014)
The existing approximate analytical methods of analyzing free-standing stairs fail to predict the distribution of any stress resultan t an d the actual three dimensional behavior of the atair slab system. A more rationale but simple and accurate method of analysis based on ffnite element method is presented. Plate flexural analysis is used to evaluate unknown displacements at each node of a rectangular plate element. Spreadsheet (FEM 2D) i also used to onalyze the stairs and to compare the finite element analysis with the analytical method. The study reveals that the variation of stress resultants across a aection is non-uniform, which is otherwise not recognized by the analytical methods. This indicates that the effects ot axial forces in flights are more than offset by the effect ot in-plane moment which causes lateral sway of the whole stair towards te upper flight